Recent Advances of Electrode Materials Applied in an Electrochromic Supercapacitor Device - Qingfu Guo; Chao Sun; Yiran Li; Kaoxue Li; Xishi Tai (Molecules)
An electrochromic supercapacitor device (ESD) is an advanced energy storage device that combines the energy storage capability of a supercapacitor with the optical modulation properties of electrochromic materials. The electrode materials used to construct an ESD need to have both rich color variations and energy storage properties. Recent advances in ESDs have focused on the preparation of novel electrochromic supercapacitor electrode materials and improving their energy storage capacity, cycling stability, and electrochromic performance. In this review, the research significance and application value of ESDs are discussed. The device structure and working principle of electrochromic devices and supercapacitors are analyzed in detail. The research progress of inorganic materials, organic materials, and inorganic/organic nanocomposite materials used for the construction of ESDs is discussed. The advantages and disadvantages of various types of materials in ESD applications are summarized. The preparation and application of ESD electrode materials in recent years are reviewed in detail. Importantly, the challenges existing in the current research and recommendations for future perspectives are suggested. This review will provide a useful reference for researchers in the field of ESD electrode material preparation and application.